The application basis of immuno-checkpoint inhibitors combined with chemotherapy in cancer treatment - Shi, Ming-Yan; Liu, Han-Ge; Chen, Xiao-Hong; Tian, Ye; Chen, Zhi-Nan; Wang, Ke (Frontiers in Immunology, 2023)
Immuno-checkpoint inhibitors (ICIs) bring a promising prospect for patients with cancers, which restrains the growth of tumor cells by enhancing anti-tumor activity. Nevertheless, not all patients benefit from the administration of ICIs monotherapy. The partial response or resistance to ICIs is mainly due to the complex and heterogenous tumor microenvironment (TME). The combined therapy is necessary for improving the efficacy of tumor treatment. Chemotherapy is reported not only to kill tumor cells directly, but also to stimulate effective anti-tumor immune responses. Several combined therapies of ICIs and chemotherapeutic agents have been approved for the first-line treatment of cancers, including PD-1/PD-L1 inhibitors. This review summarizes the potential mechanisms of the combined therapy of ICIs and chemotherapeutic agents in inducing immunogenic cell death (ICD) and reprogramming TME, and elucidates the possible anti-tumor effects of combined therapy from the perspective of metabolic reprogramming and microbiome reprogramming.